2013
DOI: 10.1002/jmv.23839
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the precore and core promoter region of the hepatitis B virus genome

Abstract: There is increasing evidence that hepatitis B virus (HBV) infections with different genotypes and subgenotypes differ in response to treatment and long-term prognosis. The differences emerge from variability within the genomes that leads to structural deviations at the pregenomic level and to changes at the translational level. Naturally occurring HBV strains covering the four major genotypes A-D were obtained from 393 patients and part of the genome was amplified using polymerase chain reaction (PCR), sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Mutations of the core promoter (CP) and precore are prevalent in HBV chronic infection 40 and the severity of liver disease associated with core promoter (T1753C, A1762T, G1764A, T1768A and A1846T/C) and precore (G1896A and G1899A) mutations has been widely discussed 4144 . BCP A1762T/G1764A are dual mutations which enhance viral genome replication 41, 42 , and may partially resist neutralization of anti-HBs. In addition to the above mutations, the frequency of mutations (G1742A, A1755C, A1775G, C1773T and T1802C) in the experimental group was significantly higher than in the control group ( p  < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of the core promoter (CP) and precore are prevalent in HBV chronic infection 40 and the severity of liver disease associated with core promoter (T1753C, A1762T, G1764A, T1768A and A1846T/C) and precore (G1896A and G1899A) mutations has been widely discussed 4144 . BCP A1762T/G1764A are dual mutations which enhance viral genome replication 41, 42 , and may partially resist neutralization of anti-HBs. In addition to the above mutations, the frequency of mutations (G1742A, A1755C, A1775G, C1773T and T1802C) in the experimental group was significantly higher than in the control group ( p  < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…During the natural course of HBV chronic infection, especially in the immunoactive phase, mutations in the core promoter (CP), precore, and core genes are most common (37). The association of hepatitis B virus mutations in the core promoter (T1753C, A1762T, G1764A, and A1846T/C) and precore regions (G1896A) with the severity of liver disease has been widely discussed (38)(39)(40)(41). The G1896A mutation resulting in reduced or absent HBeAg production may be one of the factors contributing to severe hepatitis, as both of the above mutations have been shown to upregulate viral DNA replication and reduce HBeAg production in vitro (42).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that T1858C mutations are often found in combination with A1775G ( 21 ). In our results, we showed that 16 of 17 T1858C mutation-containing sequences were in T1858C/A1775G/G1721A triple mutations.…”
Section: Discussionmentioning
confidence: 99%